The effectiveness of yoga therapy to reduce the level of depression among elderly in the community - Wachidah Yuniartika; Syamsul Anwar; Abdu Rahim Kamil; Lily Herlinah (Alma Ata University Press, 2021)
Background : Depression is one of the most common diseases among the elderly. Depression indicates disturbances in mood, physical and cognitive symptoms. Depression symptoms related to mood disorders include sadness, loss of interest in activities, worthlessness, and death, and suicidal thoughts. Early detection of depression in elderly can be noticed if the elderly have been known to possess factors that may cause depression. Yoga is a non-pharmacological therapy used to treat depression. Yoga movements consist of three stages, pranayama (breath control), asana (body temperature), and meditation (relaxation of the mind), these movements are very important to overcome stress and depression problems. Objectives : To purpose the effectiveness of yoga therapy in reducing depression in the elderly in the community. Methods : This research uses the quantitative research method with quasi-experimental with pre-test post-test design without control. The research site was in Gedongan Village, Baki Sub district, Sukoharjo, Central Java, in March-May 2021, with a total of 47 elderly using the purposive sampling method. Inclusion criteria include 60 years old, GDS score minimum 5, no extremity disorders, and Muslim. Screening for depression employed the Geriatric Depression Scale (GDS). The media used were videos and booklets, using Islamic religious classical music and data analysis used the Wilcoxon test. Results : The average depression level of respondents during the pre-test was 8.40 while the post-test decreased to 4.77 or a mean difference of 3.63 with a p-value of 0.001 (p <0.05). Yoga therapy and breathing program have a remarkable and refreshing effect. Conclusion : The conclusion is that the level of depression in the elderly resulted in a higher pre-test average value than the post-test value, which means that the level of depression after yoga therapy has decreased.